Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1039/cc9960000597
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement by water vapour of catalytic reduction of NO by propene over mechanically mixed Mn2O3 and Sn-ZSM-5

Abstract: The first example where the presence of water vapour considerably enhances the rate of the reaction NO, C3H6, O2 -+ N2, COX, H20 in the entire range of reaction temperature (250-500 "C) is found when a mechanical mixture of MnzO3 and Sn-ZSM-5 is used as a catalyst.Catalytic reduction of NO by using hydrocarbons in the presence of an excess of oxygen has attracted much attention. In addition to early reports on Cu-~eolites,l-~ many other catalysts have been reported.4-6 However, the most serious problem encount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1996
1996
1999
1999

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 3 publications
0
18
0
Order By: Relevance
“…On catalysts that are not very effective in catalyzing the equilibration of NO+O 2 and NO 2 , the rate of N 2 formation is substantially higher when the input NO x is NO 2 instead of NO. This has been observed on γ-Al 2 O 3 [1], H-ZSM-5 [1], Na-ZSM-5 [4], Ce-ZSM-5 [4], ZrO 2 [5], Ga 2 O 3 [5], Sn-ZSM-5 [6], InAl 2 O 3 [7], In-MFI [8] and Zn-MFI [9]. It has also been observed that Group II metal oxides in general are much more effective in the SCR of NO 2 compared to NO [10].…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…On catalysts that are not very effective in catalyzing the equilibration of NO+O 2 and NO 2 , the rate of N 2 formation is substantially higher when the input NO x is NO 2 instead of NO. This has been observed on γ-Al 2 O 3 [1], H-ZSM-5 [1], Na-ZSM-5 [4], Ce-ZSM-5 [4], ZrO 2 [5], Ga 2 O 3 [5], Sn-ZSM-5 [6], InAl 2 O 3 [7], In-MFI [8] and Zn-MFI [9]. It has also been observed that Group II metal oxides in general are much more effective in the SCR of NO 2 compared to NO [10].…”
Section: Introductionmentioning
confidence: 87%
“…The difficulty in explaining the results for mixture (6) does not invalidate the results given for mixtures (1) to (5). It will be shown that the SO 2 oxidation in mixture (6) has been suppressed by the hydrocarbon. The chemical kinetics calculations are presented in the next section.…”
Section: Oxidation Experimentsmentioning
confidence: 92%
See 3 more Smart Citations